A Case Report of Basal Cell Carcinoma in a Non-Sun-Exposed Area: A Rare Presentation Mimicking Recurrent Perianal Abscess. (21st November 2018) - Carr, Audrey V.; Feller, Edward; Zakka, Fouad R.; Griffith, Rogers C.; Schechter, Steven
Abstract : Basal cell carcinoma (BCC), a common malignancy, arises most often in sun-exposed areas but does rarely occur in non-sun-exposed sites. Prior tissue injury, especially sharp trauma and chronic inflammation, increases the risk of BCC. We describe a 66-year-old male patient with recurrent perianal abscesses who was found to have a large pigmented basal cell carcinoma. The mass was excised without recurrence at two-year follow-up. Perianal BCC is commonly larger at the time of diagnosis than tumors in sun-exposed sites, likely related to delay in diagnosis. Increased size can lead to increased surgical complexity and more pronounced effects on nearby structures. Early detection is important for optimal patient outcomes. In selected patients presenting with a perianal mass, basal cell carcinoma should be included on the differential diagnosis.